2009
DOI: 10.1007/s12034-009-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and photoluminescence studies of CdTe nanoparticles before and after transfer from liquid phase to polystyrene

Abstract: The major objective of this work was to detect the change of photoluminescence (PL) intensity of CdTe nanoparticles (NPs) before and after transfer from liquid phase to polystyrene (PS) matrix by electrospinning technique. Thio-stabilized CdTe NPs were first synthesized in aqueous, then enwrapped by cetyltrimethylammonium bromide (CTAB), and finally, transferred into PS matrix to form CdTe/PS nanofibres by electrospinning. Then, CdTe/PS nanofibres were characterized by scanning electron microscope (SEM) and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…15 For biological and clinical applications, quantum dots (QDs) are widely studied for various purposes including labeling, imaging, targeted drug delivery, and photodynamic therapy. [16][17][18] Various types of QDs have been extensively explored and utilized in cell-or animal-based evaluations of toxicity and biocompatibility in vitro or in vivo, even at the molecular level. [19][20][21] Cadmium-tellurium (CdTe) QDs are typical semiconductor nanomaterials with good fluorescence characteristics; they have attracted considerable attention because of their unique optical properties and their potential applications in the manufacturing of chemical sensors, optical switches, display devices, and biological labels.…”
Section: Xu Et Almentioning
confidence: 99%
“…15 For biological and clinical applications, quantum dots (QDs) are widely studied for various purposes including labeling, imaging, targeted drug delivery, and photodynamic therapy. [16][17][18] Various types of QDs have been extensively explored and utilized in cell-or animal-based evaluations of toxicity and biocompatibility in vitro or in vivo, even at the molecular level. [19][20][21] Cadmium-tellurium (CdTe) QDs are typical semiconductor nanomaterials with good fluorescence characteristics; they have attracted considerable attention because of their unique optical properties and their potential applications in the manufacturing of chemical sensors, optical switches, display devices, and biological labels.…”
Section: Xu Et Almentioning
confidence: 99%
“…The methods in Refs. [13][14][15][16][17][18][19] need strict anaerobic conditions, using NaHTe (synthesized by NaBH 4 and Te powder) as the tellurium source. This increases the complexity of the operation, due to the extreme instability of NaHTe in air.…”
Section: Discussionmentioning
confidence: 99%
“…If the methanol precipitation and aqueous re-dissolution procedure is skipped and the initial excess of the thiol stabilizer remains in solution, NWs will not develop. As a result, they reported that the chain aggregation was caused by a drop of the stabilizer concentration, so that the dynamic equilibrium between the NP binding and the free stabilizer shifted to the dissolved state [6,27]. In the present study, we explore a new strategy for CdTe NW synthesis under a specific wavelength of light and describe the entire procedure involved.…”
Section: Introductionmentioning
confidence: 97%